207k views
5 votes
HELP PLEASE !
ASAP
a=
b=
c=

HELP PLEASE ! ASAP a= b= c=-example-1
User Dieend
by
5.1k points

2 Answers

6 votes

Answer:

a = 0

b = 6

c = 4

Explanation:

f(x) = -x² + x + 6

a = -(-2)² + (-2) + 6 = 0

b = -(0)² + (0) + 6 = 6

c = -(2)² + (2) + 6 = 4

User Snieguu
by
4.6k points
3 votes

Answer:

a = 0, b = 6, c = 4

Explanation:

Given

f(x) = - x² + x + 6 , then

f(- 2) = - (- 2)² + (- 2) + 6 = - 4 - 2 + 6 = 0 ← a

f(0) = 0 + 0 + 6 = 6 ← b

f(2) = - (2)² + 2 + 6 = - 4 + 2 + 6 = 4 ← c

User Susheel Karam
by
4.7k points